Airway hyper‐responsiveness to mannitol provides a good evaluation of atopy in childhood asthma. (31st March 2015) - Attanasi, M; Rapino, D; Marcovecchio, M L; Consilvio, N P; Scaparrotta, A; Cingolani, A; Di Pillo, S; Chiarelli, F
Abstract Aim The relationship between airway hyper‐responsiveness (AHR) and atopy has been previously investigated, but there are still some issues to be clarified. The aim of this study was to assess the link between AHR and mannitol and atopy in asthmatic children. Methods We evaluated 44 children with asthma, aged 6–16 years of age, using skin prick tests (SPTs), serum total and specific immunoglobulin E (IgE) levels and the mannitol challenge test (MCT). Results We found a good correlation between AHR to mannitol and specific IgE against Dermatophagoides pteronissinus (r = −0.66, p < 0.001) and a weak correlation with specific IgE against dog dander (r = −0.33, p = 0.01) and Aspergillus fumigatus (r = −0.23, p = 0.02). Furthermore, we found a weak correlation between AHR to mannitol and serum total IgE (r = −0.30; p = 0.03), the sum of specific IgE to aeroallergens (r = −0.37, p = 0.01) and the number of positive SPTs (r = −0.31, p = 0.02). Conclusion Measuring AHR with MCT might provide an accurate evaluation of the degree of atopy in children. The patients with a higher degree of atopy were significantly more reactive to mannitol. In clinical practice, these results indicate that children with asthma who are more atopic may require more intensive treatment strategies to reduce AHR.